Shared governance increases marine protected area effectiveness - Andrea Mast; David Gill; Gabby N. Ahmadia; Emily S. Darling; Dominic A. Andradi-Brown; Jonas Geldman; Graham Epstein; M. Aaron MacNeil (PLoS ONE, 2025)
Marine protected areas (MPAs) are widely used to conserve and manage coastal resources. Protected areas are governed by a variety of institutional arrangements, yet little is known concerning the relative performance of different governance approaches. This research draws upon a unique dataset that combines details on the reported International Union for Conservation of Nature (IUCN) governance categories of 217 global MPAs and their ecological outcomes to compare the performance of alternative governance arrangements. We find that MPAs with shared governance arrangements, where management authority is shared among multiple government and non-government actors, are 98% more likely to have higher fish biomass than MPAs governed by state agencies (i.e., primarily government) alone (mean effect size and 95% C.I = 0.32 ± 0.31). We also find higher biomass in older MPAs, those in countries with higher gross domestic product (GDP), and those with a higher proportion of no-take area. With targets to protect 30% of our oceans driving new commitments to expand MPA coverage globally, our results suggest that multi-stakeholder participation and collaboration facilitated by shared and decentralized governance arrangements can play an important role in achieving conservation outcomes.